Strategic Responses to Changing Climate Change Policies: The Role Played by Carbon Accounting. Issue 2 (24th November 2017) - Bui, Binh; Fowler, Carolyn J.
Abstract: Using a broad institutional theory lens, this paper examines the climate change strategies and carbon accounting practices adopted by two New Zealand electricity firms in response to changes in government climate change policies over time (2002–12). The two firms pursue different strategic responses to climate change‐related institutional and economic pressures in order to maintain both legitimacy and a competitive advantage. Five different strategic responses are identified: avoidance, operational conformance, strategic conformance, strategic differentiation, negotiation and manipulation. Firm‐level characteristics are also important drivers of inter‐firm variations in the strategic responses. Further, carbon accounting makes the greatest contribution to carbon reduction when integrated as part of strategic processes that support strategic conformance and strategic differentiation. Carbon monitoring systems, internal carbon information use and carbon disclosure were the main forms of carbon accounting used to realise the different strategies employed. Abstract : Using an institutional lens, this study examines the strategic responses to climate change and carbon accounting practices of two New Zealand electricity generators over time. The strategic responses adopted balance the need for legitimacy and competitiveness. Carbon accounting drives significant carbon reduction when it supports a strategic conformance or differentiation strategy.